Análise da profundidade ótica de aerossóis no cerrado mato-grossense - Palácios, Rafael da Silva (2014)
Studies of the optical properties of aerosols on local scales and their relationship with solar radiation are of great importance for atmospheric research. These studies contribute to the understanding of the radiative properties and the process of transmission to the surface. One of the ways to assess the effects caused by aerosols is by analyzing their optical properties. Thus this paper provides an analysis of Aerosol Optical Depth (AOD) and the Angstrom coefficient () and estimates the Forcing Radiative of Aerosols (ARF) on the surface in a region of Cerrado in Mato Grosso. The study area is affected every year in the dry season by numerous records of outbreaks of fire. The data acquired from AERONET (Aerosol Robotic Network) were analyzed and correlated with micrometeorological variables precipitation, surface temperature and Relative Humidity. The total AOD to the wavelength of 500nm and their plots due to the fine and coarse fraction of particulate matter was correlated, concluding that the AOD in this region has a high correlation with the fine fraction of aerosols fashion, with a coefficient Spearman correlation of 0.975 with a confidence interval ranging from 0.996 to 0.981. The values obtained for the Angstrom coefficient () showed a large increase in the ratio of AOD to the particles emitted by biomass burning. We attempted to quantitatively investigate the values of ARF in a period of transition from dry-moist. The ARF values were obtained by simultaneous measurements of Aerosol Optical Depth (AOD) for the range of 500nm and solar radiation in the visible range (Sw). The peaks for AOD 500nm reached 1.6 in September where 5,576 fires in Mato Grosso were recorded. The value of ARF for the day reached 8.12.13 (-93.01 ± 8.46) Wm-2, with the variation of the AOD 500 nm in 0.1 caused a decrease of about 80 Wm-2 on the surface during the end of August and beginning of September peak ARF reached -120 Wm-2 for values above 1.0 optical depth.